RESPON PERTUMBUHAN TANAMAN TOMAT (Solonum Lycopersium L) TERHADAP PEMBERIAN PUPUK KANDANGDARI KOTORAN BABI - Wantri Niat Hati Bazikho; Nonozisokhi Gea (Jurnal Sapta Agrica, 2025)
This study aimed to investigate the effect of pig manure fertilizer on the growth and yield of tomato plants. The research was conducted from June to August 2025 using a one-factor Completely Randomized Design (CRD), with the factor being the dose of pig manure fertilizer at four levels: PK0 (no treatment), PK1 (15 tons/ha), PK2 (30 tons/ha), and PK3 (45 tons/ha). Each experimental unit consisted of six plants, resulting in a total of 72 plants observed. The parameters measured included plant height, number of leaves, and number of flowers. The results indicated that the application of pig manure fertilizer had a significant effect on all observed growth parameters. The most optimal vegetative and generative growth was observed at the PK3 dose (45 tons/ha). This dose significantly increased plant height, leaf number, and flower number compared to the other treatments. The improved growth is likely associated with the availability of macronutrients such as nitrogen (N), phosphorus (P), and potassium (K) contained in pig manure. These nutrients not only support vegetative development but also accelerate flower formation as part of generative growth. In addition to directly benefiting plant growth, the use of pig manure also contributes to improving the physical, chemical, and biological properties of the soil, such as enhancing soil fertility, structure, and microbial activity. Another advantage is its wide availability and relatively low cost, making it a practical and economical solution for farmers. This study confirms that the appropriate use of pig manure fertilizer can increase tomato productivity while supporting sustainable agricultural practices.